2016
DOI: 10.1080/02508060.2016.1166416
|View full text |Cite
|
Sign up to set email alerts
|

Desalination and water security in the US–Mexico border region: assessing the social, environmental and political impacts

Abstract: In the western US-Mexico border region, both countries' authorities look to desalination as a means to meet increased demands for dwindling supplies. In addition to several existing or planned desalination plants, plans exist to develop projects along Mexico's coasts to convert seawater into freshwater primarily for conveyance and consumption in the United States. Even though desalination systems have the potential to increase water supply in the region, there are associated consequences, costs and constraints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 18 publications
(23 reference statements)
0
15
0
1
Order By: Relevance
“…Meanwhile, desalination sceptics believe that water conservation, improved water use efficiency in all sectors, and water management should be initially considered to achieve water security (Wilder et al, ). The main concerns are the high capital, operating costs of running desalination plants and the environmental problems.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, desalination sceptics believe that water conservation, improved water use efficiency in all sectors, and water management should be initially considered to achieve water security (Wilder et al, ). The main concerns are the high capital, operating costs of running desalination plants and the environmental problems.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their coastal location, Denmark, Australia, and Abu Dhabi have the option to discharge brine into the sea. Brine disposal can potentially harm marine ecosystems (Elimelech & Phillip, ; Wilder et al, ), though some studies in Israel showed that brine disposal into the Mediterranean Sea caused limited harm (Shemer & Semiat, ; Tal, ). These studies showed that environmental impacts to marine life were limited to the immediate brine discharge area (Miller, Shemer, & Semiat, ; Tal, ).…”
Section: Important Future Considerationsmentioning
confidence: 99%
“…Options for mitigating the negative effects of brine disposal from seawater desalination operations include using multiport diffusers that disperse the brine through multiple outlets from the discharge pipeline (National Research Council, ; Wilder et al, ). If a seawater desalination plant is intertwined with a thermal powerplant, the powerplant's outgoing cooling water could be mixed with brine effluent to dilute the mixture as it enters the sea (Elimelech & Phillip, ).…”
Section: Important Future Considerationsmentioning
confidence: 99%
“…In fact, the human populations of the USA's Southwest and northern Mexico might find themselves in a truly revolutionary early-21st Century situation whereby independence from all freshwater extraction macro-problems related to the Colorado River is achievable under neart-term future meteorological circumstances [23]. Surely, governmental budgeteers will be pleased, as will taxpayers, and commercial circles will certainly take notice of persuasively influential new economic facts [24][25][26][27].…”
Section: Optimizing Northern Mexico-southern California's Freshwater mentioning
confidence: 99%